An eco-structuralism approach in soundscape (data) composition - Gomes, J.A.; Barbosa, A.; Penha, R. (ACM International Conference Proceeding Series, 2014)

Design for Classroom Units: A Collaborative Multicultural Studio Development with Chinese Students - Caires, C. S.; Barbosa, A.; Hanyou, W. (International Journal of Educational and Pedagogical Sciences, 2020)
Design for Classroom Units: A Collaborative Multicultural Studio Development with Chinese Students

Murky shooting: The use of auditory (non-speech) feedback on mobile audiogames - Cordeiro, J.; Baltazar, A.; Barbosa, A. (ACM International Conference Proceeding Series, 2012)

NIME education at the school of arts of the portuguese catholic university/CITAR - Martins, L.G.; Barbosa, A. (Proceedings - 2013 Learning and Teaching in Computing and Engineering, LaTiCE 2013, 2013)

Privacy in sound-based social networks - Cordeiro, J.; Barbosa, A. (Communications in Computer and Information Science, 2014)